Noise Effects on a Proposed Algorithm for Signal Reconstruction and Bandwidth Optimization - Ashour, Ahmed; Khalaf, Ashraf A. M.; Hussein, Aziza I.; F. A. Hamed, Hesham; Ramadan, Ashraf (International Journal of Electrical and Computer Engineering Systems, 2023)
The development of wireless technology in recent years has increased the demand for channel resources within a limited spectrum. The system’s performance can be improved through bandwidth optimization, as the spectrum is a scarce resource. To reconstruct the signal, given incomplete knowledge about the original signal, signal reconstruction algorithms are needed. In this paper, we propose a new scheme for reducing the effect of adding additive white Gaussian noise (AWGN) using a noise reject filter (NRF) on a previously discussed algorithm for baseband signal transmission and reconstruction that can reconstruct most of the signal’s energy without any need to send most of the signal’s concentrated power like the conventional methods, thus achieving bandwidth optimization. The proposed scheme for noise reduction was tested for a pulse signal and stream of pulses with different rates (2, 4, 6, and 8 Mbps) and showed good reconstruction performance in terms of the normalized mean squared error (NMSE) and achieved an average enhancement of around 48%. The proposed schemes for signal reconstruction and noise reduction can be applied to different applications, such as ultra-wideband (UWB) communications, radio frequency identification (RFID) systems, mobile communication networks, and radar systems.